Clostridium difficile Enteritis after Total Abdominal Colectomy for Ulcerative Colitis - Hassan Nasser; Semeret Munie; Dania Shakaroun; Tommy Ivanics; Surya Nalamati; Keith Killu (Case Reports in Critical Care)
Introduction. Isolated Clostridium difficile small bowel enteritis is a rare condition with significant morbidity and mortality. Presentation of Case. An 83-year-old female with refractory ulcerative colitis underwent a total proctocolectomy and end ileostomy. Her postoperative course was complicated with return to the operating room for repair of an incarcerated port site hernia. Subsequently, she developed septic shock and multiorgan failure requiring intubation and mechanical ventilation, renal replacement therapy, and high dose vasopressors. Diagnostic workup revealed diffuse small bowel wall thickening on computed tomography scan as well as positive nucleic acid amplification test for C. difficile toxin B gene. Despite treatment with antibiotics and maximum attempts at resuscitation, the patient expired. Discussion. C. difficile infection most commonly affects the colon but rarely can involve the small bowel. The pathogenesis of C. difficile enteritis is unclear but is believed to mirror that of colitis. Surgical patients are susceptible for C. difficile infection, as they tend to be relatively immunosuppressed in the postoperative period. Radiologic findings of enteritis may mimic those of colitis and this includes small bowel dilation and thickening. Treatment for this condition has not been well established but it is approached similar to colitis. Conclusion. Despite an increase in the number of case reports of C. difficile enteritis, it continues to be a rare but potentially fatal infection. Clinicians should maintain a high index of suspicion especially in patients with inflammatory bowel disease who undergo colon resections.